Provisions For Perishing The Sold Property Before Delivery And Its Implications - Hamad, Adeed Ezzat . Ezzat; Adeed, Marawan (جامعة الوادي - University of Eloued, 2024)
(is one of the important and ” Destruction of Sale before Delivery"The topic active topics generally in civil law and especially in the sale contract. The importance of this topic is explained in terms of various aspects.First,it takes place too much in the practical life.Second, it represents the core of sale contract and all the rules of sale contract is about this topic.This topic concerns with the destruction that happens in a period between making sale contract and before its delivery to a buyer. A number of juristically lawful theories and others of Islamic Sharia have appeared which tackle and arrange the destruction rules of sale before delivery.These theories are differentiated in how they tackle the destruction rules of sale before delivery according to the bases of these theories.These affect the lawful legislations.So,the last one is different also from others in the way of its arrangement and tackling the rules of destruction.
مقال
Keywords: the majeure force ; sudden state; sale; commitment ; The Promise